THE PHENOMENON OF ALIENATION IN CHILDREN-PARENT RELATIONS - E. Е. Ivanova; Yu. A. Storozheva (Вестник университета)
The main approaches to the definition of the phenomenon of “alienation” have been considered. The causes and dynamics of the emergence of alienation in the child-parent relationship have been investigated. Interconnection of violations in parent-child relationships with the incorrect educational strategy of parents has been revealed. Special attention has been paid to the specificity of manifestations and the nature of alienation in adolescence. It has been supposed about the connection between alienation and style of upbringing of a teenager. The practical part of the article describes the procedure and results of the study on the determination of this connection. The analysis has identified a statistically significant interrelation between alienation and the relationship between parents and children. Critical importance of hypo-care for the formation of teenage alienation has been ascertained. The characteristic of child-parent relations in same-sex and opposite-sex couples child-parent has been made.